Anak Zina Dalam Pandangan Islam - Moh. Ali Ghafir (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Adultery is a child born of a mother resulting from a relationship that does not follow the rules of syara’ or the outcome of a forbidden relationship. Children resulting from unmarried relationships, have the same degree in the sight of Allah as the other servants. He is very likely to be a happy person in the world and in the hereafter if he can actualize himself to be a pious person. An illegitimate child is a servant of God who must be respected, he has no difference with the other servants of God. It's just that he was born of irresponsible people. In this case the sin is both perpetrators. Babies who are born will not bear the slightest sin of committing adultery.